PENGARUH AROMATERAPI MINYAK ATSIRI JAHE TERHADAP KADAR TRIGLISERIDA DAN KOLESTEROL DARAH TIKUS YANG DIBERI PAKAN TINGGI LEMAK - Aji Agung Cahyaji (Wahana Peternakan, 2017)
The study aims to determine the effect of ginger (Zingiber officinale) essential oil via inhalation on blood triglyceride, total cholesterol, High Density Lipoprotein (HDL) cholesterol, and Low Density Lipoprotein (LDL) cholesterol level of rats that fed high fat diet. Eighteen albino rats (Rattus norvegicus) were devided into three treatments groups. The treatments were K1 (standard diet) as negative control, K2 (high fat diet) as positive control, and K3 (high fat diet + ginger essential oil inhalation). Blood samples were collected after 5 weeks of treatment period. The result showed the level of triglyceride, cholesterol, and HDL cholesterol at treatment K3 tend to be lower than treatment K2. LDL cholesterol level at treatment K3 show higher result than treatment K2. From the result of this study cocluded that inhalation of ginger essential oil can lowering triglyceride, total cholesterol, and LDL cholesterol level and raise HDL cholesterol level. Keywords: triglyceride, cholesterol, HDL cholesterol, LDL cholesterol, ginger essential oil